Assessment of local agricultural innovation networks in Camajuani, Cuba, from a feminist approach (Islas, 2021)
With the Cuban Revolution, Cuban rural women dignify themselves in public and private spaces through social and economic policies, programs and strategies; however, there are dissatisfactions and contradictions towards female empowerment in the local agricultural innovation networks in the municipality of Camajuani, in Villa Clara. In the face of this situation, it is intended an assessment of the local agricultural innovation networks in Villa Clara from a feminist approach. The assessments reveal masculinization of the agricultural innovation networks, patriarchal and anti-feminist agricultural culture marked by a complacent discourse addressed to the lack of innovations with a gender equity approach to include more women in agriculture.
Keywords: agriculture; feminism; innovation networks